Extended resection of a plasmocytoma of bone and an amyloidoma of the chest wall - Safi, Seyer; Winkel, Jan op den; Schnabel, Philipp Albert; Hegenbart, Ute; Neben, Kai; Schneider, Thomas; Dienemann, Hendrik (The annals of thoracic surgery, 2013)
Solitary plasmocytoma of bone is a rare condition of plasma cell neoplasia that presents as a single lesion. Amyloidoma of the chest wall is an uncommon presentation of solitary tissue amyloid deposition in the absence of systemic light-chain amyloidosis. This report describes a patient with both uncommon conditions. The tumor originated from the spine and invaded the right lung. In this exceedingly rare case, radiotherapy and a two-step resection of the right lower lobe, full-thickness chest wall, diaphragm, and vertebral body of T9 provided local control of the tumor. Spondylodesis of T7 to T11 provided spine stability.
Gesehen am 25.01.2022